2001
DOI: 10.1017/s1047951101000336
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of expenditures on, and utilization of resources in, health care in adults with congenital heart disease

Abstract: Our study has provided pilot data on the economic outcomes for patients with congenital heart diseases. We have identified parameters that could predict expenditure, but which will have to be examined in future research. This is needed to develop guidelines for health insurance for those with congenital heart diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 11 publications
0
35
2
Order By: Relevance
“…16,26,27 A study by Lee and colleagues 26 revealed that adolescents whose parents overprotect or underestimate them have higher levels of depression. Adolescents' chronic diseases can impose physical, psychologic, and economic burdens on families; these can affect the relationship between adolescents and parents and thus change parental attitudes, becoming either overprotective or hostile toward adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,26,27 A study by Lee and colleagues 26 revealed that adolescents whose parents overprotect or underestimate them have higher levels of depression. Adolescents' chronic diseases can impose physical, psychologic, and economic burdens on families; these can affect the relationship between adolescents and parents and thus change parental attitudes, becoming either overprotective or hostile toward adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents' chronic diseases can impose physical, psychologic, and economic burdens on families; these can affect the relationship between adolescents and parents and thus change parental attitudes, becoming either overprotective or hostile toward adolescents. 16 This, in turn, can cause social and emotional problems in the adolescents themselves, which makes it difficult for them to live with their diseases. 28 The findings of this study show that parental attitude is correlated with both depression and resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…quent mortality. 17,18 Risk assessment has the potential to assist therapeutic targeting and appropriate resource allocation for ACHD services.…”
Section: Exercise Intolerance Identifies Patients At Risk Of Hospitalmentioning
confidence: 99%
“…Adults with congenital heart disease are complex and have greater comorbidities and higher admission rates compared with the general patient population. [3][4][5][6][7] This complexity often contributes to the increased utilization of health care resources. Despite the important role that pediatric hospitals play in the care of patients with congenital heart disease, resource utilization of adult patients who undergo congenital heart surgery in pediatric hospitals is understudied.…”
mentioning
confidence: 99%